RESEARCH ON MEDICAL TERMINOLOGY IN UZBEK LINGUISTICS: QUALITATIVE AND QUANTITATIVE ANALYSIS (Scientific journal of the Fergana State University, 2024)
The article examines dissertations devoted to the study of medical terminology in Uzbek linguistics. To date, a total of fourteen monographic studies have been identified, and their qualitative and quantitative analysis has been carried out. Their chronological order was also illustrated using a diagram. In these scientific papers, it is established that medical terms are studied in ten areas of linguistics, in which the definition of semantic characteristics of industry units is the highest priority. It follows that the aspect of the meaning and content of medical terms is in the focus of special attention of researchers. This scientific study proved that the field of medical terminology in Uzbek linguistics began on a monographic scale in 1967 and was formed in stages, covering various fields of linguistics, such as linguoculturology, linguopragmatics, linguopoetics. In addition, achievements and shortcomings in this area were demonstrated.